Role of silicon oxide defects in emission process of Si-SiO₂ systems - Baran, M.; Bulakh, B.; Korsunska, N.; Khomenkova, L.; Yukhymchuk, V.; Sheinkman, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Si-rich SiO₂ films prepared by r.f. magnetron sputtering and annealed at 1150 °C are investigated by photoluminescence, Raman and EPR methods. It is found that emission spectrum of as-prepared samples contains one broad infrared band. It is shown that one-year aging in ambient air and low-temperature annealing in oxygen atmosphere lead to the increase of infrared band intensity and the appearance of additional bands with maxima at 1.7 eV, 2.06 eV and 2.3 eV while annealing in hydrogen atmosphere results in the decrease of 1.7 eV and 2.06 eV band intensities. The decrease of crystallite sizes results in high-energy shift of infrared band while the peak positions of another ones (at 1.7, 2.06 and 2.3 eV) do not change. It is concluded that infrared band is connected with Si crystallites while another ones can be ascribed to silicon oxide defects, 1.7 and 2.06 eV bands being ascribed to oxygen-excess defects such as EX- and non-bridging oxygen hole centres.